Activity of LY146032 in vitro and in experimental enterococcal pyelonephritis. - Miniter, P M (1987)
The efficacy of LY146032 (LY), a new lipopeptide antibiotic, was compared with that of vancomycin, ciprofloxacin, ceftriaxone, imipenem, and gentamicin and combinations of LY-ceftriaxone, LY-imipenem, and LY-gentamicin against 15 strains of Streptococcus (Enterococcus) faecalis by microtiter dilution and checkerboard techniques. LY was effective within a very narrow range of drug concentrations (from 0.125 to 2.0 micrograms/ml) and was more active than other agents tested against S. faecalis. Enhanced inhibition of S. faecalis was seen more frequently with combinations of either penicillin or ampicillin and an aminoglycoside than with combinations of LY and gentamicin, imipenem, or ceftriaxone. The in vivo efficacy of LY was compared with that of vancomycin and ampicillin alone and combinations of vancomycin-gentamicin, ampicillin-gentamicin, and LY-gentamicin in a rat model of chronic enterococcal pyelonephritis. At a dose of 10 mg/kg given twice daily, LY reduced the number of organisms per kidney significantly compared with that in infected untreated controls within 48 h after the initiation of therapy. At 20 mg/kg given once a day, LY was less effective but reduced colony counts significantly after 4 days of therapy, and its activity was comparable to that of vancomycin or vancomycin-gentamicin given twice daily. LY may be a promising agent for the treatment of enterococcal infections.